306 Rationale and evidence for emerging antibody-drug conjugates in gynecological cancers: effect of online education on clinician knowledge. (4th December 2020) - Fisher, Geoff; Furedy, Amy; Vandenbroucque, Juliette; Concin, Nicole
Abstract : Introduction/Background: A number of targeted antibody drug conjugates (ADCs) are emerging with the potential to become important new treatment strategies for gynecological cancers, including recurrent/resistant ovarian and cervical cancers. This study determined whether online continuing medical education could improve the knowledge of oncologists and obstetricians/gynaecologists (obs/gyns) on the rationale and evidence for emerging ADCs. Methodology: A 30-minute online video lecture was launched for physicians outside the USA in December 2019. Data was collected to March 2020. Educational effect assessed with repeated-pairs pre-/post-activity, where individual participants served as their own control. 3 multiple-choice, knowledge questions and 1 self-efficacy, 5-point Likert scale confidence question were analyzed. Chi-squared test assessed pre- to post-activity change (5% significance level, P <.05). Magnitude of change in total number of correct responses overall, and for each question, were determined with Cramer's V (<.06=Modest, 0.06–0.15=Noticeable, .16-.26=Considerable, >.26=Extensive). Results: 49 oncologists and 154 obs/gyns completed pre- and post-activity questions. A positive educational effect was observed for oncologists (considerable effect, V=.217, P=.0002) and obs/gyns (noticeable effect, V=.097, p=.0028) with average% of correct responses increasing 40 to 62% for oncologists and 34 to 43%, for obs/gyns. Participants with 3/3 answers correct increased from pre- to post-activity (6 to 35% for oncologists and 6 to 12%, for obs/gyns). Improvements in% of correct responses post-activity were seen for all 3 knowledge-based questions on antigen targets, and key trial data for tisotumab vedotin and mirvetuximab vedotin (88%, 39%, 45% improvements for oncologists; 70%, 15%, 16% improvements for obs/gyns). Confidence in knowledge of ADCs also improved post-activity with a total average confidence shift of 38% for oncologists and 32% for obs/gyn. 62% of oncologists' and 44% of obs/gyns' responses were reinforced or improved post-activity. 34% of all participants stated they would modify treatment plans as a result of participation in the activity. Conclusion: This on-demand, online video lecture resulted in a positive education effect for both oncologists and obs/gyns. However, persistent knowledge gaps are evident, especially amongst obs/gyns, suggesting there is a need for additional education as data on ADCs continues to emerge. Online medical education is valuable in establishing improved knowledge of emerging therapies, such as ADCs, as well as identifying areas of continued educational need. Disclosures: Supported by an independent education grant from GenMab and Seattle Genetics. Geoff Fisher, Amy Furedy, and Juliette Vandenbroucque have no relevant financial relationships. Nicole Concin, has served as an advisor for AstraZeneca, Seattle Genetics and Mersana, and received travel expenses from Amgen, Genmab, and Roche.